A modified method for immediate loading and reinforced metal framework overdenture: clinical case - Gennari Filho, Humberto; Mazaro, José Vitor Quinelli; Goiato, Marcelo Coelho; Turcio, Karina Hekga Leal (ARCHIVES OF HEALTH INVESTIGATION, 2016)
The aim of the present study was to report a modified protocol for immediate implant-supported full-arch rehabilitation on three interforaminal implants and two implants placed in the posterior mandible, one on each side. This article describes a treatment protocol that can be used to reduce the time required for the fabrication and placement of an implant-supported prosthesis. It is described a technique that improved patient comfort when compared to conventional technology and propose the possibility of using a denture with internal reinforcement framework with captured abutments. Descriptors: Dental Implants; Immediate Dental Implant Loading; Denture, Complete.